PLURALISM, TOLERANCE AND NEW AGE - Marsudi Utoyo (Muhammadiyah Law Review Journal, 2017)
Understanding of religious pluralism that is taught in the context of Pancasila is a perspective seats the all religions in the same position so that the position of all religions in equal assume. Islam, Catholicism, Protestantism, Hinduism, Buddhism, Confucianism, other religions and beliefs based understanding local cultures is a reality that still exists in Indonesia. Pluralism is carried here departs from socio-religious, in which religious pluralism as a basis that bring forth to respect other religions and other beliefs that exist in Indonesia. In Article 29, paragraphs 1 and 2 of the Constitution of the Republic of Indonesia in 1945, the state provides the freedom and tolerance on the life of religious freedom. The cornerstone of religious life is based orthopraxis religious life meaning, truth, glory, and majesty of God Almighty which we live and ring in the faith that we profess, should be evident in the praxis of everyday life in the form of attitudes and religious tolerance.